2023
DOI: 10.1371/journal.ppat.1011441
|View full text |Cite
|
Sign up to set email alerts
|

The methylglyoxal pathway is a sink for glutathione in Salmonella experiencing oxidative stress

Abstract: Salmonella suffer the cytotoxicity of reactive oxygen species generated by the phagocyte NADPH oxidase in the innate host response. Periplasmic superoxide dismutases, catalases and hydroperoxidases detoxify superoxide and hydrogen peroxide (H2O2) synthesized in the respiratory burst of phagocytic cells. Glutathione also helps Salmonella combat the phagocyte NADPH oxidase; however, the molecular mechanisms by which this low-molecular-weight thiol promotes resistance of Salmonella to oxidative stress are current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Thus far, studies focusing on S. pyogenes, S. mutans, and S. sanguinis have shown gloA to be the primary modulator of MG tolerance in vitro with gloB mutants having little effect (63,84). This is in support of what was observed with L. monocytogenes, but not Salmonella where it was found that gloB was more important for Salmonella resistance to oxidative stress and killing by macrophages (64,95).…”
Section: Discussionsupporting
confidence: 62%
“…Thus far, studies focusing on S. pyogenes, S. mutans, and S. sanguinis have shown gloA to be the primary modulator of MG tolerance in vitro with gloB mutants having little effect (63,84). This is in support of what was observed with L. monocytogenes, but not Salmonella where it was found that gloB was more important for Salmonella resistance to oxidative stress and killing by macrophages (64,95).…”
Section: Discussionsupporting
confidence: 62%
“…This high level of glyoxalase redundancy, particularly in Cbei and Cpas point to a possible important role of these enzymes in both organisms. Because of their strict anaerobic nature [30-31], Clostridium species are particularly susceptible to oxidative damage, which might explain the preponderance of glyoxalases (in Cbei and Cpas ), which play an important role in countering oxidative stress [32-33]. In the glyoxalase system, methylglyoxal is converted to D -lactate via S - D -lactoylgluthatione and eventually to pyruvate [29, 34].…”
Section: Discussionmentioning
confidence: 99%